Coming Out to Parents in Lesbian and Bisexual Women: The Role of Internalized Sexual Stigma and Positive LB Identity - Baiocco, Roberto; Pistella, Jessica; Morelli, Mara (Frontiers in Psychology, 2020)
The experience of “coming out” (CO) to parents is often a crucial event in the lives of lesbian and bisexual (LB) women, associated with lower internalized sexual stigma (ISS) and higher positive LB identity. Few studies have compared the experiences of LB women in the CO process. Rather, most prior research has either: (1) not addressed bisexuality or eliminated bisexual individuals from the analysis; (2) combined bisexual women and bisexual men in the same sexual orientation group; or (3) examined bisexual participants alongside lesbian women and gay men, using a single monolithic measure. Thus, the present research aimed at investigating the role of ISS and positive LB identity in inhibiting or encouraging CO to parents in a sample of 241 lesbian women (Mage = 27.61, SD = 7.19) and 186 bisexual women (Mage = 25.23, SD = 5.81), aged 18–40 years. Most participants reported that they had already revealed their sexual orientation to their mother (69%) and their father (52%). More lesbian women had CO to both their mother and their father than had bisexual women. These lesbian women reported lower levels of ISS and higher levels of LB positive identity relative to bisexual women. On average, CO to mothers occurred at age 20 (SD = 5.54), while CO to fathers occurred at age 22 (SD = 5.63). LB women did not differ in the average age of CO to mothers or fathers, or in parental reactions to CO. Finally, ISS was found to affect the process of CO to both parents via positive identity (bootstrapping estimate = –.26, SE = .08, 95% CI = –.43, .11), whereas sexual orientation was not found to moderate the path from ISS to CO to both parents. The present study contributes to our understanding of the differences between LB women when developing their sexual orientation, highlighting the relevance of a positive LB identity for CO to parents. Research and clinical implications and directions for future research are discussed.